Micro-ring resonator made by ion exchange technique and detecting benzene (C6H6), propanol (C3H7OH) and methane (CH4) as cladding layer - Ariannejad, Mohammad Mahdi; Akbari, Elnaz; Amiri, Iraj Sadegh (IOP Publishing, 2018)
We proposed and investigated the use of a micro-ring resonator in an ion exchange waveguide as a gas/liquid sensor. The ion exchange process in an optical waveguide was simulated using IONEX software, where Ag+ ionic concentrations were deposited on glass substrates. Subsequently, a micro-ring resonator was designed on the ion exchange waveguide as a transducer to sense changes in the effective refractive index using different cladding materials. Benzene, propanol and methane, which exhibit different refractive indices, were used as cladding materials. According to the simulation results, a change in the refractive index causes a change in the spectrum peak intensity as well as a resonance shift. The trace of spectrum change against the refractive index allows the proposed design to be used for gas/liquid sensors. Other micro-ring resonator parameters - FSR, FWHM, Q-factor, finesse and Δf - were also investigated. Results show that changes in the refractive index vary with the parameter. As a result, the proposed design also exhibits great potential for other areas, especially for tunable terahertz generation.